A CASE REPORT OF UTERINE MYOMA CAUSING NON-PURPURAL UTERINE INVERSION - Fantahun, Yitbarek; Haile, Sofanit; Kebede , Eskinder; Teklu, Sisay (Ethiopian Journal of Reproductive Health, 2021)
Uterine inversion is a condition where the uterus is inverted downward with prolapse of the fundus into the endometrial cavity and to the cervix. It is broadly classified as puerperal and nonpuerperal based on the cause of the uterine inversion with puerperal uterine inversion being a more common type of inversion. Here is a rare form of non-puerperal uterine inversion with fundal submucous myoma. Keyword: Haultain’s method, Myoma, Uterine inversion.